ВЛИЯНИЕ ФУНКЦИ ПЕЧЕНИ НА ФАРМАКОКИНЕТИКУ β-БЛОКАТОРОВ У БОЛЬНЫХ С ИШЕМИЧЕСКОЙ БОЛЕЗНЬЮ СЕРДЦА И СОЧЕТАННОЙ ПАТОЛОГИЕЙ - Л. С. Литвинова; С. В. Бабак; Е. В. Кириенкова; А. А. Корженков; Н. И. Самаров; О. Л. Носарева; Т. С. Прохоренко; Е. В. Коновалова; В. Д. Якушина; А. И. Дмитриева; Ю. В. Колобовникова; В. А. Серебрякова; et al. (Архивъ внутренней медицины, 2013)
The aim of our study is detection of the possible correlation between the degree of inflammation, fibrosis of the liver and the level plasma concentration of metoprolol in the treatment of chronic heart disease. Terminal stages of liver fibrosis characterized by marked reduction of effector T cell function and activity of cells with the potential suppressor (CD4+CD25+), and B-lymphocytes and NK-cells (CD16+SD56+), which play the main role in a cascade of liver damage. In the prolonged ischemia, metabolism of metoprolol is slows and its concentration in the blood is gradually increasing, which subsequently may lead to a enhanced pharmacological effects of metoprolol and more significant blocking of β-receptors.